Development of a Field Guidebook for Pollinator Insects on Palawija Plants in Dolat Rayat District - Dewi Sri Lestari Sigalingging; Syarifuddin Syarifuddin; Syahmi Edi (Publikasi Indonesia, 2021)
This study was aimed to determine the feasibility of a field guide book for pollinating insects of crop plants in the Subdistrict of Dolat Rayat, Karo District, which is suitable for undergraduate students majoring in Biology. This research is a development research with a 4D model (Thiagarajan) which consists of 4 stages, namely: define, design, develop, and deseminate, in research only up to the develop stage. The field guidebook developed was validated based on the content aspects and presentation, scored 94% or very feasible, while the learning design was scored 90% (very feasible) and the graphic 83% (very worthy). The Entomology lecturers' responses was of 68% (feasible) . The results of individual trials for the field guidebook was 92% (very feasible), 91% (very feasible) and 92% (very feasible) in the larger group. That the field guide book for pollinator insects in crop plants for the Subdistrict of Dolat Rayat is very feasible thus can be used by students as a guide book to learn to recognize pollinator insects of the crop plants in the Dolat Rayat District.